Deoiled algal biomass derived renewable sugars for bioethanol and biopolymer production in biorefinery framework. (January 2020) - Naresh Kumar, A.; Chatterjee, Sulogna; Hemalatha, Manupati; Althuri, Avanthi; Min, Booki; Kim, Sang-Hyoun; Venkata Mohan, S.
Graphical abstract: Highlights: Deoiled algal biomass as feedstock for bioethanol and biopolymer production. Hydrolysis of deoiled algal biomass for production of reducing sugars. Integrated approach for maximum resource recovery from algal biomass. Sustainable microalgae based bioprocess in a biorefinery framework. Abstract: The present study is designed to evaluate the potential of deoiled algal biomass (DAB) residue as an alternative resource for the production of bioethanol and biopolymers in a biorefinery approach. Hybrid pretreatment method resulted in higher sugar solubilization (0.590 g/g DAB) than the corresponding individual physicochemical (0.481 g/g DAB) and enzymatic methods (0.484 g/g DAB). Subsequent utilization of sugars from hybrid pretreatment for bioethanol using Saccharomyces cerevisiae  resulted in maximum bioethanol production at pH 5.5 (0.145 ± 0.008 g/g DAB) followed by pH 5.0 (0.122 ± 0.004 g/g DAB) and pH 6.0 (0.102 ± 0.002 g/g DAB). The experiments for biopolymer (PHB: polyhydroxybutyrate) production resulted in 0.43 ± 0.20 g PHB/g DCW. Extracted polymer on NMR and FT-IR analysis showed the presence of PHB. Exploration of DAB as an alternative renewable resource for multiple biobased products supports sustainability and also enables entirety use of DAB by addressing the DAB-residue allied disposal issues.